Pandemic and Roman Law. Remembering Emperor Justinian and the Corpus Iuris Civilis - Solís Gózar, Julio Santiago (2020)
We are living in a time of intellectual crisis, where it is believed that the study of Roman law is unnecessary and we vehemently trust in the aphorism orabunt causa melius which defines a rabula but not a jurist, since the latter does not pay exclusive attention to the law because it knows that it will become an inanimate being, an instrument of repetition of decrees and codes, which has lost interest in knowing the origin of legal institutions and has lost the taste for legal culture and as a consequence, has also lost «auctoritas» to practice the profession. On this occasion we will invite the reader to reflect on the importance of Roman law and we will provide information on the pandemic that occurred in the 6th century, remembering Justinian and his greatest undertaking, the Corpus Juris Civilis.